Single Motherhood in Postwar Soviet Russia: Cultural Code and its Literary Implication. (3rd July 2022) - Sergeev, Dmitrii
ABSTRACT: The purpose of the paper is to reveal the development of cultural code of single motherhood in postwar Russia through the analysis of fiction. The research turns on the assumption that cultural codes might be deciphered only through a process of semiosis. The cultural code of single motherhood has been forged in a contradictory environment. Though officially accepted by way of 1944 law, Soviet single mothers found themselves in an ambiguous context: urged by the state to give birth to children and under pressure from traditional family values. Using the result of content analysis of 12 short stories, novels and novellas written by female Soviet authors between 1959 and 1984 I reconstruct the cultural code of post-war Soviet single motherhood. The analysis identifies 11 meaningful facets around which the code was centred. Putting stories in a chronological order contributes to unravelling the evolving, functioning and principles of code.